2019
DOI: 10.15761/bem.1000169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Extremely-Low-Frequency Electromagnetic Field (ELF-EMF) on Growth of Bacteria Escherichia coli

Abstract: The goal of this work was to evaluate the biological effect of the extremely-low-frequencies. We started by evaluating the effect of frequencies with the anti-bacterial functions listed in the Rife frequency database on the growth of Escherichia coli. Among the 11 sets of frequencies tested, we found that only one set comprising frequencies below 100 Hz showed a significant effect on the growth of E. coli, and it was an enhancement effect instead of an inhibition on growth. We further tested various sets of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…In our study, the resonance frequency effects of 0.5Hz were investigated at various exposure times, with 60min of exposure causing the death of all C. minutus cells within 48h of incubation. Previous research on cyanobacteria determined that Anabaena circinalis and Cylindrospermopsis raciborskii were most susceptible to growth inhibition by ELF-EMFs at a resonance frequency of 0.7Hz (Chen et al, 2019). In addition, our research revealed that 0.5Hz ELF-EMF decreased the chlorophyll-a concentration in C. minutus cell cultures.…”
Section: Discussionsupporting
confidence: 58%
“…In our study, the resonance frequency effects of 0.5Hz were investigated at various exposure times, with 60min of exposure causing the death of all C. minutus cells within 48h of incubation. Previous research on cyanobacteria determined that Anabaena circinalis and Cylindrospermopsis raciborskii were most susceptible to growth inhibition by ELF-EMFs at a resonance frequency of 0.7Hz (Chen et al, 2019). In addition, our research revealed that 0.5Hz ELF-EMF decreased the chlorophyll-a concentration in C. minutus cell cultures.…”
Section: Discussionsupporting
confidence: 58%
“…Exposure to ELF electromagnetic waves (40-100 Hz) for 1 hour can increase the growth of E. coli bacteria, but after 16 hours of exposure, it has decreased (Chen et al, 2019). ELF-EMF exposure with a frequency of 7 Hz can inhibit cell growth in Anabaena culture compared to controls.…”
Section: Introductionmentioning
confidence: 94%
“…Interaksi yang terjadi antara materi biologi dengan medan elektromagnetik ELF dapat berefek bahaya, yang dipengaruhi oleh faktor frekuensi maupun panjang gelombang, kepadatan medan serta waktu paparan. Adapun faktor penting lain yang juga berpengaruh terhadap dampak buruk interaksi tersebut yaitu status fungsional, sensitivitas materi biologi yang terpapar, jarak dari sumber radiasi dan vaskularisasi bagian yang diradiasi juga perlu dipertimbangkan (Boga et al, 2016;Y. Chen et al, 2019;Min et al, 2021).…”
Section: Pendahuluanunclassified